The Effect of Bioorganic Dosage with N, P Fertilizer on Rice Production of Sri Methods and Increased Nutrient Content of Paddy Soil Intensification - Nelson Elita; Rita Erlinda; Agustamar Agustamar (Jurnal Ilmu dan Teknologi Terapan Pertanian, 2020)
The System of Rice Intensification (SRI) operates under aerobic conditions so that helpful microbes are active and abundant. Effective N-fixing rhizobacteria and indigenous phosphate solubilizers Azotobacter and Pseudomonas grow well in the organic compost Bioorganic because it resembles their natural habitat. The purpose of this research is to find out the right dose of Bioorganic fertilizer and the most N and P doses needed to optimize the SRI method of rice crop production. This research uses a factorial randomized block design. The first factor is Bioorganic fertilizer dosage (1, 3, and 6) t ha-1. The second factor is the dose of N and P fertilizers to use (0, 25, 50, and 75)% of the recommended dosage. The results of this study inform you about Bioorganic fertilizers containing Azotobacter and Pseudomonas fluorescens indigenous. Azotobacter bacteria produce the availability of nutrients N, which functions as Plant Growth Promoting Rhizobacteria (PGPR), these bacteria quickly colonize the root system, regulate hormonal balance, nutrition, and encourage resistance to pathogens. Pseudomonas fluorescens bacteria acts as a provider of phosphorus and nutrients in the generative phase. Both of these microbes have a role in SRI method of rice plant metabolism to increase vegetative and generative growth of rice plants with SRI method with production reaching production of 8.80 t ha-1 in B2 (3 t ha-1) and N2P2 (50%) with the production of 9.21 t ha-1, so the use of inorganic fertilizers is more efficient. Rice soil nutrient status increased pH from slightly acidic to neutral, C-organic increased from 1.27% (low) to 9.30-10.68% (high), N total from 0.13% (low) to 0.45-0.58% (high), P- available from 13.0 ppm reaching 18.0-20.0 ppm (moderate), the Bioorganic application has not been able to increase the C: N, CEC value and base saturation. Nutrient uptake of N and P on the leaves of rice plants is better at dose B2. Bioorganic applications increase the nutrient content of paddy soils planted with the SRI method compared to initial soil nutrient analysis.